Having permission not to remember: perspectives on interventions for post-traumatic stress disorder in the absence of trauma memory. Issue 1 (31st December 2022) - May, Hannah; Paskell, Rachel; Davies, Catrin; Hamilton-Giachritsis, Catherine
ABSTRACT: Background: It is possible for people to have post-traumatic stress disorder (PTSD) without memory of the trauma event, such as in drug-facilitated sexual assault. However, there is little evidence available on treatment provision for this population. Objective: This study aimed to address this gap by exploring the experiences of people who have had psychological intervention for PTSD without memories (PwM). Method: Interpretative phenomenological analysis was used to explore the lived experience of nine women with PwM, who had sought psychological assessment/therapy. Participants were recruited via social media and completed semi-structured interviews online/via telephone. Results: Identified themes concerned two broad areas: (i) the challenges of having therapy whilst lacking memories and (ii) what was helpful in therapy. Challenges included: delayed help-seeking; having emotional/sensory reactions in the absence of recognisable triggers; experiencing therapy as more applicable to remembered trauma (vs. unremembered); and difficulty discussing and processing unremembered trauma. However, participants also described helpful aspects of therapy including: feeling safe and supported; working with emotional and sensory forms of experience; having scientific explanations for trauma and memory; and having 'permission' from therapists not to remember. Conclusions: Recommendations for clinicians included: being aware that clients with PwM may have more difficulty accessing treatment and perceive it as less applicable to them; focussing on clients' emotions and sensations (not cognitive memories) in therapy; and supporting clients to develop a more self-compassionate understanding of their experiences and lack of memory, thus supporting them to accept that not remembering is 'permitted'. HIGHLIGHTS: Having therapy for unremembered trauma involves unique challenges, but aspects of therapy can still be helpful. Suggested 'dos and don'ts' for therapists include recognising the additional barriers to treatment, focussing on emotions (not memories), and normalising memory loss